The challenge of producing progressive teachers in Malaysia: a case study of reflective writings among UPSI student teachers - Wong, Yeou Min; Rosnidar Mansor; Syakirah Samsudin (Faculty of Social Sciences and Humanities, UKM,Bangi, 2015)
Because Malaysia is determined to produce high quality teachers who are able to become agents of change and empowered decision makers about their teaching practices, it becomes the responsibility of teacher education institutions in the country to train teachers to be reflective. This study examines 428 self-reflection notes (SRNs) of seven student teachers (STs) sampled from Sultan Idris Education University (UPSI) during their teaching practicum. Semi-structured interviews were carried out to gauge the STs’ perceptions of the SRNs and identify the problems faced by them during reflection. The main aspects of the SRNs were feedback and assessment, lesson implementation, lesson preparation, classroom management and professional attributes. The reflection level of the STs was analyzed based on Van Manen’s categorization using content analysis of the SRNs reflective components. The findings revealed that majority of the research participants were barely reflective as their SRNs were mostly exhibiting at technical level. There were also SRNs that were at practical level but none of them had achieved the highest (critical) level of reflection. Among the problems encountered by STs when reflecting were the absence of a given format in writing SRNs, time constraints, workload problems, difficulty in suggesting recommendations to overcome problems, lack of guidance from supervising lecturers, and problems in determining aspects of focus in the SRNs.